2012
DOI: 10.1071/ch11451
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Metal Oxide Cluster-Surface Modified Titanium(IV) Dioxide Photocatalysts

Abstract: The surface modification of TiO 2 with molecular sized metal oxide clusters has recently been shown to be a promising approach for providing TiO 2 with visible-light activity and/or improved UV activity. This short review summarizes the effects of the surface modification of TiO 2 with the oxides of iron and tin selected from d-and p-blocks, respectively, on the photocatalytic activity. Fe(acac) 3 and [Sn(acac) 2 ]Cl 2 chemisorption on the TiO 2 surface occurs by ligand-exchange and ion-exchange, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…No obvious change in the light absorbance of TiO 2 is observed after the surface modification with tin species. This is in accordance with theoretical calculation results of molecularsized SnO 2 clusters adsorbed on anatase surfaces [37], indicating tin oxide derived states do not appear inside the TiO 2 energy gap and thus lead to no shift of light absorption. However, it cannot be excluded that the tin-related electronic states may be close to the CB of TiO 2 and thus do not exert a large influence on the optical absorption of TiO 2 [21], which is in line with the low tin content.…”
Section: Resultssupporting
confidence: 90%
“…No obvious change in the light absorbance of TiO 2 is observed after the surface modification with tin species. This is in accordance with theoretical calculation results of molecularsized SnO 2 clusters adsorbed on anatase surfaces [37], indicating tin oxide derived states do not appear inside the TiO 2 energy gap and thus lead to no shift of light absorption. However, it cannot be excluded that the tin-related electronic states may be close to the CB of TiO 2 and thus do not exert a large influence on the optical absorption of TiO 2 [21], which is in line with the low tin content.…”
Section: Resultssupporting
confidence: 90%
“…Similar shifts in the VB edge for other metal oxide-nanocluster modified TiO 2 are explained on the basis of the formation of new VB states coming from the oxide nanocluster. [17][18][19][20][21] This interfacial electron transfer causes efficient charge carrier separation contributing to the increases in the photocatalytic activities and the reduction in the TiO 2 Figure 12. Atomic structure, adsorption energy in eV and Ti 3d and Cu 3d projected electronic density of states (PEDOS) for anatase TiO2 modified with CuO, Cu2O2 and Cu4O4 clusters Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that FeO x and NiO cluster-surface modified TiO 2 prepared by the chemisorption-calcination cycle (CCC) technique shows high photocatalytic activities under illumination of visible-and UV-light. [17][18][19][20][21] In both the systems, strong dependence of the photocatalytic activity on the loading amount of the clusters is observed, [17][18][19][20][21] but the reason has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former, for example, displays a narrowed band gap, giving visible light absorption compared with pure TiO 2 . [24] The paper by Beniamino Iandolo and Michael Zäch from Chalmers University of Technology ('Enhanced Water Splitting on Thin-Film Hematite Photoanodes Functionalized with Lithographically Fabricated Au Nanoparticles') highlights why hematite or iron oxide (a-Fe 2 O 3 ) is arguably preferable to Co and Mn as a catalyst in the race for development of a commercially viable device for water splitting-based solar fuels because of its low cost, high stability, abundance, and potentially high solar-to-hydrogen conversion efficiency. [25] A focus on the practical commercial realities of water splitting technologies also characterises the paper from Alex Izgorodin, Orawan Winther-Jensen, and Douglas MacFarlane of Monash University ('On the Stability of Water Oxidation Catalysts: Challenges and Prospects').…”
Section: Institutional Approachesmentioning
confidence: 99%